IPB BIODIVERSITY INFORMATICS (IPBIOTICS) UNTUK PEMBANGUNAN BERKELANJUTAN - Ervizal A.M. Zuhud; Yeni Herdiyeni; Agus Hikmat; Abdul Haris Mustari; Arya A. Metananda; Desta S. Pravista; Mayanda Mega; Rahmat Setiawan (Media Konservasi, 2014)
Indonesia is the country with the second highest biodiversity in the world. It is not only the diversity of biodiversity, but also diversity of indigenous knowledge such as functional foods and other traditional ingredients. IPB as one of the leading university in Indonesia has important role in the management of natural resources of biodiversity. Currently, management of biodiversity resource require an integrated and holistic system using computer science and technology which develop rapidly at this time. This study developed a system of biodiversity informatics IPB (IPBiotics) for biodiversity information management of indonesia’s natural resources in order to improve the knowledge management (knowledge management), exploration, analysis, synthesis and interpretation of data ranging from the level of genomic biodiversity, species level to the ecosystem level. Activities undertaken in this research include exploration of organism, biodiversity database development and biodiversity informatics infrastructure using model Resources Descriptions framework RDF with biodiversity data standards. Taxonomic Databases Working Group (TDWG). IPBiotics participatory and integrated. Some of the features of the application that was developed in organism such as IPBiotics system, location mapping and exploration missions. IPBiotics also uses computer vision technology in application development. By IPBiotics we hope that the data information and knowledge of indonesian natural wealth can be utilized appropriately and optimally, so that the preservation of natural resources can be properly maintained. Keywords: Biodiversity informatics, Computer vision, Databases, IPBiotics, Sustainability.